Genotype-Environment Interaction Analysis of NQO1, CYP2E1, and NAT2 Polymorphisms and the Risk of Childhood Acute Lymphoblastic Leukemia: A Report From the Mexican Interinstitutional Group for the Identification of the Causes of Childhood Leukemia - Medina-Sanson, Aurora; Núñez-Enríquez, Juan Carlos; Hurtado-Cordova, Eduardo; Pérez-Saldivar, María Luisa; Martínez-García, Anayeli; Jiménez-Hernández, Elva; Fernández-López, Juan Carlos; Martín-Trejo, Jorge Alfonso; Pérez-Lorenzana, Héctor; Flores-Lujano, Janet; Amador-Sánchez, Raquel; Mora-Ríos, Felix Gustavo; et al. (Frontiers in Oncology, 2020)
Background. Acute lymphoblastic leukemia (ALL) is the main type of cancer in children. In Mexico and other Hispanic populations, the incidence of this neoplasm is one of the highest reported worldwide. Functional polymorphisms of various enzymes involved in the metabolism of xenobiotics have been associated with an increased risk of developing ALL, and the risk is different by ethnicity. The aims of the present study were to identify whether NQO1, CYP2E1, and NAT2 polymorphisms or some genotype-environmental interactions were associated with ALL risk in Mexican children. Methods. We conducted a case-control study including 478 pediatric patients diagnosed with ALL and 284 controls (children without leukemia). Ancestry composition of a subset of cases and controls was assessed using 32 ancestry informative markers. Genetic-environmental interactions for the exposure to hydrocarbons were assessed by logistic regression analysis. Results. The polymorphisms rs1801280 (OR 1.54, 95% CI 1.21–1.93), rs1799929 (OR 1.96, 95% CI 1.55–2.49) and rs1208 (OR 1.44, 95% CI 1.14–1.81) were found to increase the risk of ALL; being the risks higher under a recessive model (OR 2.20, 95% CI 1.30–1.71, OR 3.87, 95% CI 2.20–6.80 and OR 2.26, 95% CI 1.32–3.87, respectively). Gene-environment interaction analysis showed that NAT2 rs1799929 TT genotype confers high risk to ALL under exposure to fertilizers, insecticides, hydrocarbon derivatives, and parental tobacco smoking. No associations among NQO1, CYP2E1 and ALL were observed. Conclusion. Our study provides evidences for the association between NAT2 polymorphisms/ gene-environment interactions and the risk of childhood ALL in Mexican children.